The role of serine protease HtrA in acute ulcerative enterocolitis and extra-intestinal immune responses during Campylobacter jejuni infection of gnotobiotic IL-10 deficient mice - Heimesaat, Markus M.; Alutis, Marie; Grundmann, Ursula; Fischer, André; Tegtmeyer, Nicole; Böhm, Manja; Kühl, Anja A.; Göbel, Ulf B.; Backert, Steffen; Bereswill, Stefan (Frontiers in Cellular and Infection Microbiology, 2014)
Campylobacter jejuni infections have a high prevalence worldwide and represent a significant socioeconomic burden. C. jejuni can cross the intestinal epithelial barrier as visualised in biopsies derived from human patients and animal models, however, the underlying molecular mechanisms and associated immunopathology are still not well understood. We have recently shown that the secreted serine protease HtrA plays a key role in C. jejuni cellular invasion and transmigration across polarised epithelial cells in vitro. In the present in vivo study we investigated the role of HtrA during C. jejuni infection of mice. We used the gnotobiotic IL-10-/- mouse model to study campylobacteriosis following peroral infection with the C. jejuni wild-type strain NCTC11168 and the isogenic, non-polar NCTC11168ΔhtrA deletion mutant. Six days post infection (p.i.) with either strain mice harboured comparable intestinal C. jejuni loads, whereas ulcerative enterocolitis was less pronounced in mice infected with the ΔhtrA mutant strain. Moreover, ΔhtrA mutant infected mice displayed lower apoptotic cell numbers in the large intestinal mucosa, less colonic accumulation of neutrophils, macrophages and monocytes, lower large intestinal nitric oxide, IFN-γ and IL-6 as well as lower TNF-α and IL-6 serum concentrations as compared to wild-type strain infected mice at day 6 p.i. Notably, immunopathological responses were not restricted to the intestinal tract given that liver and kidneys exhibited mild histopathological changes six days p.i. with either C. jejuni strain. We also found that hepatic and renal nitric oxide levels or renal TNF-α concentrations were lower in the ΔhtrA mutant as compared to wild-type strain infected mice. In conclusion, we show here that the C. jejuni HtrA protein plays a pivotal role in inducing host cell apoptosis and immunopathology during murine campylobacteriosis in the gut in vivo.